Detection and Validation of Circular DNA Fragments Using Nanopore Sequencing - Tüns, Alicia Isabell; Hartmann, Till; Magin, Simon; González, Rocío Chamorro; Henssen, Anton George; Rahmann, Sven; Schramm, Alexander; Köster, Johannes (Frontiers in Genetics, 2022)
Extra-chromosomal circular DNA is a phenomenon frequently observed in tumor cells, and the presence of circular DNA has been recognized as a marker of adverse outcome across cancer types. We describe a computational workflow for identification of DNA circles from long-read sequencing data in different tumor model systems. The workflow is implemented based on the Snakemake workflow management system. Its key step uses a graph-theoretic approach to identify putative circular fragments. Using nanopore sequencing of selectively enriched circular DNA, we demonstrate robustness and selectivity of our approach. As a positive control, we demonstrate that we recover the mitochondrial genome, which is the only DNA in normal human cells that regularly exists in circles. Using spike-in experiments with plasmid-based circular DNA, we show high selectivity and sensitivity of our method. Finally, we show that the workflow facilitates detection of larger circular DNA fragments containing extrachromosomal copies of the MYCN oncogene and the respective breakpoints, which is a potentially useful application in disease monitoring of several cancer types.